The impact of an early intervention on vocabulary, phonological awareness, and letter–sound knowledge among Spanish-speaking kindergarteners. (16th December 2020) - Porta, María Elsa; Ramirez, Gloria
ABSTRACT: This study examined the impact of two different interventions: Phonological Awareness PA–only versus PA, vocabulary, and Morphological Awareness (MA) on Spanish-speaking kindergarteners' language and literacy skills. We took measures on PA, vocabulary, letter-name and sound knowledge, and MA. Children in the comprehensive intervention condition showed significant growth from pretest to posttest on all measures and an overall vocabulary knowledge advantage over children in the PA-only intervention. Children in the PA condition showed significant growth on vocabulary out of context, letter-name sound knowledge, initial syllable identity, and rhyme identity. Results support the integration of PA, vocabulary, and MA in kindergarten interventions. The importance of including MA in kindergarten vocabulary interventions and the feasibility of classroom interventions by trained teachers are discussed.